Barriers in Technology Integration: EFL Lecturers and Students’ Experience in English Learning and Instruction amidst Covid-19 Pandemic Disruption - Rana Taneta Putri; Sofendi; Soni Mirizon (Universitas Pendidikan Ganesha, 2022)
Since Covid-19 Pandemic outbreak all schools and universities in Indonesia were closed and teaching-learning activities were shifted to online learning mode. Learning from home trend started to dominate classroom instruction in all level of education. In university, this phenomenon certainly affected lecturers and students’ enthusiasm in teaching-learning activities since they need to make necessary adaptations in many aspects including the use of technology to support learning. Online learning requires technology to apply the digital tools or media. This study was aimed at finding out the barriers that lecturers and students faced in integrating the technology in teaching during the midst of Covid-19 Pandemic disruption. This study used qualitative research method in a case study design. The data were collected using observation and interview with the participants in one of public university. The participants of this study were EFL lecturers and students of one public university. Two EFL lecturers and ten students from two different classes took part as participants of the study. The data were analyzed using thematic analysis. The findings of the study showed that there were two barriers faced by the lecturers and students in integrating the technology in online learning such as extrinsic barriers and intrinsic barriers. In extrinsic barriers there was resources barrier and in intrinsic barriers there were improve the students’ knowledge and skills in online learning barrier, the barrier to control the student’s attitude while online learning and the assessment barrier in integration the technology.